Suppression of heterotrimeric G-protein β-subunit affects anther shape, pollen development and inflorescence architecture in tobacco - Pes̆kan-Berghöfer, Tatjana; Oelmüller, Ralf (Planta, 2005)
The role of the heterotrimeric G-protein β-subunit in plant development was studied in transgenic tobacco (Nicotiana tabacum L.) plants with reduced β-subunit levels due to the antisense expression of the β-subunit mRNA. The antisense plants had aberrant anther shape and produced non-germinating pollen. The anthers were sporadically transformed to petals, whereas other floral organs were not affected. The pollen grains were smaller than the wild-type pollen and had abnormal cell walls. The architecture of mature antisense plants was altered. The plants had long branched panicles and short stems. These data suggest that the β-subunit of the plant heterotrimeric G-proteins is involved in the regulation of the reproductive phase of the tobacco life cycle, particularly in stamen development and pollen maturation.